Stress Granule-Mediated Oxidized RNA Decay in P-Body: Hypothetical Role of ADAR1, Tudor-SN, and STAU1 - Alluri, Ravi Kumar; Li, Zhongwei; McCrae, Keith R. (Frontiers in Molecular Biosciences, 2021)
Reactive oxygen species (ROS) generated under oxidative stress (OS) cause oxidative damage to RNA. Recent studies have suggested a role for oxidized RNA in several human disorders. Under the conditions of OS, mRNAs released from polysome dissociation accumulate and initiate stress granule (SG) assembly. SGs are highly enriched in mRNAs, containing inverted repeat (IR) Alus in 3’ UTRs, AU rich elements and RNA-binding proteins. SGs and processing bodies (P-bodies) transiently interact through a docking mechanism to allow exchange of RNA species. However the types of RNA species exchanged, as well as the mechanisms and outcomes of exchange are still unknown. Specialized RNA binding proteins, including adenosine deaminase acting on RNA (ADAR1-p150), with affinity toward IR Alus, and Tudor staphylococcal nuclease (Tudor-SN) are specifically recruited to SGs under OS along with an RNA transport protein, Staufen1 (STAU1), but their precise biochemical roles in SGs and SG/P-body docking are uncertain. Here we critically review relevant literature and propose a hypothetical mechanism for the processing and decay of oxidized-RNA in SGs/P-bodies, as well as the role of ADAR1-p150, Tudor-SN and STAU1.